2020
DOI: 10.1021/acs.langmuir.0c02835
|View full text |Cite
|
Sign up to set email alerts
|

Design of Surfactant Tails for Effective Surface Tension Reduction and Micellization in Water and/or Supercritical CO2

Abstract: Interfacial properties and water-in-CO2 (W/CO2) microemulsion (μE) formation with double and novel triple tail surfactants bearing trimethylsilyl (TMS) groups in the tails are investigated.Comparisons of these properties are made with those for analogous hydrocarbon (HC) and fluorocarbon (FC) tail surfactants. Surface tension measurements allowed for critical micelle concentrations (CMC) and surface tensions at the CMC (γCMC) to be determined, resulting in the following trend in surface activity FC > TMS > HC.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 55 publications
0
5
0
Order By: Relevance
“…SANS experiments allowed to link this directly to the effective packing parameter of the system and the concomitant change of the hydrophilic/CO 2 -philic balance. 411 Still more recently doubleand triple-tailed surfactants containing trimethylsily (TMS) groups in their tail were shown to also be able to form microemulsions with water and CO 2 , 412 which is interesting as it allows to formulate fluorine-free microemulsions, which is relevant from an environmental point of view.…”
Section: Nonclassical Microemulsionsmentioning
confidence: 99%
“…SANS experiments allowed to link this directly to the effective packing parameter of the system and the concomitant change of the hydrophilic/CO 2 -philic balance. 411 Still more recently doubleand triple-tailed surfactants containing trimethylsily (TMS) groups in their tail were shown to also be able to form microemulsions with water and CO 2 , 412 which is interesting as it allows to formulate fluorine-free microemulsions, which is relevant from an environmental point of view.…”
Section: Nonclassical Microemulsionsmentioning
confidence: 99%
“…The consequences show that the interaction energy between CO 2 and the wall increases significantly with the injection of CO 2 and is far greater than that between the oil and the wall. This is mainly caused by the properties of rock surface and CO 2 , which supercritical CO 2 becomes more polar while CO 2 is usually non-polar . This mechanism contributes to enhancing the electrostatic interaction between CO 2 and the wall, causing more CO 2 to desorb oil .…”
Section: Resultsmentioning
confidence: 99%
“…This is mainly caused by the properties of rock surface and CO 2 , which supercritical CO 2 becomes more polar while CO 2 is usually non-polar. 42 This mechanism contributes to enhancing the electrostatic interaction between CO 2 and the wall, causing more CO 2 to desorb oil. 43 As shown in Figure 5a, due to the presence of notches in the connected pore, the interaction energy of oil and wall in the 3 nm pore at the initial moment is less than that of the small pores in the double pore and the single pore systems.…”
Section: ■ Introductionmentioning
confidence: 99%
“…In earlier studies, surfactants having TMS-terminated tails were found to generate very low surface energies (surface tensions), and comparable to short fluorocarbons in water (the limiting aqueous surface tension is 22.8 mN/m for the double TMS-chain terminated surfactant AOTSiC) [39]. As an example application of low surface energy surfactants, superspreading of aqueous solution on polyvinylidene difluoride (PVDF) surface was demonstrated by using the TMS surfactant [40,41]. Therefore, combining these two functions together, polymer films prepared with TMS-bearing ProDOTSiMe3 and ProDOT(SiMe3)2 thiophene monomers are expected to exhibit superhydrophobicity as well as oleophobicity as found uniquely with fluoro-polymers [41 42].…”
Section: Figure 1 Structures Of Thiophene Monomers Having Trimethylsi...mentioning
confidence: 99%